Potensi Arkeologis di Situs Wai Ujan, Kecamatan Wulandoni, Kabupaten Lembata, Nusa Tenggara Timur - Hamdan Hamado (Tumotowa, 2021)
The Wai Ujan site is administratively included in the area of Belobao Village, Wulandoni District, Lembata Regency, East Nusa Tenggara. The problem in this research is what are the archaeological remains and what is the typology of archaeological remains contained in the site. The purpose of this study was to determine the type and typology of archaeological remains at the Wai Ujan site. This research is an early stages research that is exploratory archaeological data. The method used in this study was a field survey. Data analysis included form analysis and technology. The results showed that the types of archaeological remains found at the Wai Ujan site were stone artifacts and pottery fragments. The stone artifact findings consisted of percutor, core stone, and shale artifacts, while the pottery fragment findings consisted of closed and open containers representing the shape of a pot, bowl, and pasu.